Interactive Models in Synthetic Biology: Exploring Biological and Cognitive Inter-Identities - Bich, Leonardo (Frontiers in Psychology, 2020)
The aim of this paper is to investigate the relevance and implications of synthetic models for the study of the interactive dimension of minimal life and cognition, taking into consideration how the use of artificial systems may contribute to an understanding of the way in which interactions may affect or even contribute to shape biological identities. To do so, this paper analyses experimental work in synthetic biology on different types of interactions between artificial and natural systems, more specifically: between protocells and between biological living cells and protocells. It discusses how concepts such as control, cognition, communication can be used to characterise these interactions from a theoretical point of view, which criteria of relevance and evaluation of synthetic models can be applied to these cases, and what are their limits.